Analisis Putusan Perkara Tindak Pidana Penganiayaan yang Menyebabkan Kematian (Studi Kasus Putusan Nomor : 454/Pid.B/2024/PN.Sby Dan 1466 K/Pid/2024) - Ryan Afriansyah; Bintang Wicaksono Ajie (Decisio: Jurnal Ilmiah Hukum, 2026)
This study examines the basis for judges' considerations in criminal assault cases resulting in death, focusing on the Surabaya District Court Decision Number 454/Pid.B/2024/PN.Sby and the Supreme Court Decision Number 1466/K/Pid/2024. Using a normative-empirical approach, this research combines primary data from court observations with secondary data from laws, books, and journals. The findings show that judges' decisions in both cases rely on legal, sociological, and philosophical considerations. Legal considerations involve the prosecutor's indictment, court revelations, and valid evidence. Sociological aspects focus on societal conditions and the social impact of the decision. Philosophical considerations are based on justice, legal certainty, and utility. A comparative analysis of the District Court and Supreme Court decisions reveals differences in interpreting the elements of the charges, especially regarding the perpetrator's intent (dolus) and the causal link between the defendant's actions and the resulting consequences.